Strategy for Implementing Business Ethics in Family-Based MSMEs - Sari, Permana (International Conference On Economics Business Management And Accounting (ICOEMA), 2023)
This study examines the implementation strategy of business ethics in family-based MSMEs in Indonesia. Family businesses are an interesting phenomenon in the MSME industry with their significant contribution to the country's economic growth. Family-based MSMEs are also vulnerable to competition and ambiguous regulation implementation, which can encourage unethical business practices. This study conducted a literature analysis to identify the strengths, weaknesses, opportunities, and threats associated with implementing business strategies in family-based MSMEs. The study results show that strong family values and organizational flexibility are the main strengths supporting business ethics implementation. However, there are areas for improvement regarding limited resources and the need for more awareness about implementing business ethics. In facing opportunities, family-based MSMEs can take advantage of increased consumer awareness about business ethics and seek support from relevant parties. Regulatory challenges and intense competition remain threats that must be overcome. Based on this analysis, a business ethics implementation strategy for family-based MSMEs to respond to future economic challenges was created with the EKCELlent strategy design formulated as an easy-to-remember and attractive strategy design for family-based MSME owners, consisting of EthixEdu, KultivasiEthix, ClearCom, EthixRewards, and LeadEthix.